2020
DOI: 10.1007/s10661-020-8143-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental pollution with fluorine compounds on the level of fluoride in soil, feed and eggs of laying hens in Central Pomerania, Poland

Abstract: The present study was aimed at evaluating fluorine contamination of the eggs of free-ranging laying hens in Northern Poland, in the Central Pomerania region, in relation to the distance from the emission sources. Fluorine levels in the soil, feed, and the shells, and contents of the eggs were assayed with the potentiometric method using an ion-selective electrode from ORION Ion Meter. The sampled eggs were subjected to pressure microwave digestion with the use of a Milestone MLS-1200 microwave. All the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Anand-2 (Brahmbhatt and Patel, 2013). have also been demonstrated by Singh et al, (2013); Alim et al (2017) and Ahmed et al (2018); Elżbieta et al (2020). According to Hong et al (2016); Justyna et al (2020) fluoride produced negative impacts on the morphology, physiology and even caused death of cells.…”
Section: Resultsmentioning
confidence: 79%
“…Anand-2 (Brahmbhatt and Patel, 2013). have also been demonstrated by Singh et al, (2013); Alim et al (2017) and Ahmed et al (2018); Elżbieta et al (2020). According to Hong et al (2016); Justyna et al (2020) fluoride produced negative impacts on the morphology, physiology and even caused death of cells.…”
Section: Resultsmentioning
confidence: 79%
“…Fluorine impurities were also present on the surfaces of all the eggshell-based materials (Figure S6). It was reported that the fluorine (present in potable H2O and the feed components) consumed by laying hens often ends up in the eggshell during its mineralization [52]. In addition, the presence of Ag and Mn on the Ag-MnO2 catalyst surfaces indicates the successful formation of the catalytic materials (Figure S6).…”
Section: Surface Chemistrymentioning
confidence: 99%
“…Consequently, drinking water, which may also be artificially fluoridated as a public health measure, and food are major sources of fluoride uptake in humans. The degree of fluoride exposure is affected by the quality of food and water, the amount consumed, as well as individual variability [ 36 , 37 , 38 , 39 ].…”
Section: Fluoride As An Environmental Toxinmentioning
confidence: 99%